Decision-making systems and criteria - Matanov Muhammad Charshamievich (Genius Journals, 2022)
Decision support systems and the discovery of hidden knowledge and logical decision criteria based on decision rules and precedent are reviewed.
Keywords: Hidden knowledge; data mining; informative symptoms; neuron systems